Global Governance in Accounting - Zimmermann, J. author. aut Link
XVIII, 246 p. 16 illus.
Keywords: This book takes a look at the world of accounting and examines business's relationship with the state. It compares the accounting regulations in Germany, the UK and the US to provide evidence that privatization and convergence must be used with caution, at least in the world of accounting.